An exact analysis of chemical reaction and porosity effects for mixed convective magnetohydrodynamics Casson fluid - Nur Fatihah, Mod Omar; Zulkhibri, Ismail; Rahimah, Jusoh; Muhammad Azrin, Ahmad; Ahmad Qushairi, Mohamad (Yildiz Technical University, 2026)
In this research, we explore the Casson fluid flow under mixed convection in a plate undergoing acceleration within a porous medium, considering the effects of chemical reaction and magnetisation. The investigation encompasses heat and mass transfer characteristics, incorporating thermal radiation and chemical reactions. Inspired by the previous studies of the chemical reaction and porosity of magnetohydrodynamic Casson fluid, the focus of this research revolves around the Casson parameter with convective double diffusion flows with magnetohydrodynamics (MHD) over a plate undergoing acceleration within a porous medium, considering the occurrence of a radiative chemical reaction. Ordinary differential equations are transformed from the governing partial differential equations through appropriate non-dimensional variables to facilitate mathematical analysis. Subsequently, the Laplace transform method is utilised to get the solution for the resulting non-dimensional ordinary differential equations system. The study provides graphical representations illustrating the behaviour of various physical parameters. The trend reveals that the rising Casson parameter will descend the fluid velocity, primarily attributed to the elevated fluid viscosity. Notably, the Casson parameter has no impact as the fluid approaches the centre between the bounding surfaces. Additionally, it is seen that a higher Casson parameter results in behaviour resembling that of a Newtonian fluid. On top of that, the velocity increases significantly for larger chemical reaction coefficient values. Finally, it is noticed that velocity tends to decrease as the porosity parameter decreases and the magnetic field strength increases.